Special meetings on the situation in Spain (circular) - Citrine, Walter, 1887-1983
016a-0058-001 Telegraphic Address: TRADUNIC, SOWEST- LONDON Telephone: VICTORIA 6261 (4 LINES) The TRADES UNION CONGRESS GENERAL COUNCIL General Secretary SIR WALTER CITRINE, K.B.E. (To whom all communications should be addressed) Your Ref: Our Ref: WMC/MT/650 Department: Secretary's TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. 1st March, 1937. TO THE MEMBERS OF THE GENERAL COUNCIL. Dear Sir (Madam), SPECIAL MEETINGS ON THE SITUATION IN SPAIN. Will you please note that a Joint Meeting of the General Council of the Trades Union Congress, the National Executive Committee of the Labour Party and the Executive Committee of the Parliamentary Labour Party will be held in the House of Commons, Committee Room No. 10, on Tuesday, 9th March, at 5 p.m. The following day, a Conference will take place of the International Federation of Trade Unions and the Labour and Socialist International in connection with the Spanish situation, which will be held in the Library at the Central Hall, Westminster, S.W.1. on Wednesday, 10th March, commencing at 10 a.m. and continuing on the following day, 11th March. In accordance with the decision of the National Council of Labour, all members of the General Council of the Trades Union Congress, the National Executive Committee of the Labour Party and the Executive Committee of the Parliamentary Labour Party, are being invited to attend this International Conference, but questions involving decisions on the terms of resolutions and policy will be reserved for the General Council and the National Executive Committee only. It has also been decided to hold a Demonstration at 7.45 p.m. on Wednesday 10th March, at the Kingsway Hall, Kingsway, London, W.C.2. for the purpose of raising money for the International Solidarity Fund. In view of the importance of these meetings, I hope you will make a point of being present. Yours sincerely, WALTER CITRINE. General Secretary. 292/946/16a/59